An evidence-based approach to provide essential and desirable components to develop surveys on Sudden Unexpected Death in Epilepsy (SUDEP) for doctors: A focused review. (March 2023) - Watkins, LV; Ashby, S; Hanna, J; Henley, W; Laugharne, R; Shankar, R.
Highlights: SUDEP Counselling by clinicians is a recognised & important aspect of epilepsy care. Surveys globally have identified challenges in clinicians delivering counselling. It is important to have a common question set in this significant area of epilepsy care. This review of 16 SUDEP counselling surveys covers 4000 doctors across 30 countries. The study focus group including expert by experience outline 10 essential questions. Abstract: Sudden Unexpected Death in Epilepsy (SUDEP) is a major concern for people with epilepsy, their families, their care givers, and medical professionals. There is inconsistency in the SUDEP counselling doctors provide, compared to what is recommended in clinical guidelines. Numerous national and international surveys have highlighted how epilepsy professionals, usually doctors, deliver SUDEP risk counselling, particularly, when they deliver it and to whom. These surveys help understand the unmet need, develop suitable strategies, and raise awareness among clinicians with the eventual goal to reduce SUDEPs. However, there is no standardised survey or essential set of questions identified that can be used to evaluate SUDEP counselling practice globally. This focused review analyses the content of all published SUDEP counselling surveys for medical professionals (n=16) to date covering over 4000 doctors across over 30 countries and five continents. It identifies 36 question themes across three topics. The questions are then reviewed by an expert focus group of SUDEP communication experts including three doctors, an expert statistician and SUDEP Action, an UK based charity specialising in epilepsy deaths with a pre-set criterion. The review and focus group provide ten essential questions that should be included in all future surveys inquiring on SUDEP counselling. They could be used to evaluate current practice and compare findings over time, between services, across countries and between professional groups. They are provided as a template to download and use. The review also explores if there is a continued need in future for similar surveys to justify this activity.